Determinan Keputusan Konsumen dalam Membeli Rumah: Studi Kasus di Graha Amaris Victory - Putra , Tatas Arya; Khoirudin, Rifki; Khasanah , Uswatun (Journal of Economics, Assets, and Evaluation, 2024)
This study was conducted to determine the factors that influence consumer decisions in buying a house at Graha Amaris Victory. The total population in this study was 162 consumers with a sample of 62 which was calculated using the Slovin formula. Data collection was carried out using a questionnaire. Then, it was analyzed using Multiple Linear Regression. The results of this study indicate that: Simultaneously, all independent variables X1 (price), X2 (income), X3 (facilities), X4 (location), and X5 (environment) have a joint and significant influence on variable Y1 (purchase decision). This is evidenced by the value of F count (25.92) > F table (2.36) with significance (0.0000) <0.05. The entire independent variable is also able to explain the model by 69.8%, this is indicated by the R-Squared value of 0.6983. Partially, variable X1 (price) has no effect on variable Y1 (purchase decision). However, variables X2 (income), X3 (facilities), X4 (location), and X5 (environment) have a significant effect on variable Y1 (purchase decision) in Graha Amaris Victory Housing. For this reason, companies must map potential customers in promoting their products, ensure that the facilities offered are complete and in accordance with consumer needs, locations that are easily accessible, and a safe, comfortable, and clean environment.